Investigation of the confined-doped fiber on single-mode operating and power scaling in all-fiber single-frequency amplifiers - Li, Wei; Ren, Shuai; Deng, Yu; Chen, Yisha; Lu, Yao; Liu, Wei; Ma, Pengfei; Pan, Zhiyong; Chen, Zilun; Lei Si,; Zhou, Pu (Frontiers in Physics, 2022)
In this paper, we proposed a strategy for achieving all-fiber single-frequency amplifiers with near-diffraction-limited beam quality by using confined-doped fiber. Benefiting from the large mode area (LMA) and mode selection properties of the confined-doped fiber, the stimulated Brillouin scattering (SBS) and transverse mode instability (TMI) effects were comprehensively suppressed. Based on this confined-doped fiber assisted amplifier, a 322 W SBS-limited single-frequency laser was obtained with M2 factor of 1.25/1.33 for the x/y direction. Comparing with the full-doped fiber assisted one, the TMI threshold of the confined-doped one is improved more than 1.6 times. Overall, the technique of confined-doped in the fiber core provides a promising approach for the power scaling and single-mode operation of all-fiber single-frequency lasers.